Injection Molding of Biodegradable Deciduous Teeth Dental Post - Min-Wen Wang; Meng-Kun Xu; Stratain Era Hasfi (Applied Sciences, 2025)
Dental caries can cause premature loss of deciduous teeth, affecting children’s growth and development. Endodontic treatment using polymer posts is an effective solution. This study explores biodegradable root canal posts made from Polylactic Acid (PLA), Polycaprolactone (PCL), and amorphous calcium phosphate (ACP), aiming to enhance mechanical properties, minimize polymer degradation acidity, and prevent inflammation. A root canal post with a spherical head and serrated structure was designed and produced via micromolding and optimized using the Taguchi experimental method. The melt temperature, injection speed, and holding speed were analyzed for their influence on shrinkage, revealing an optimal rate of 2.575%, representing the sum of axial and radial shrinkage. The melt temperature had the highest impact (55.932%), followed by holding speed (33.575%), with there being minimal effect from injection speed. The composite exhibited a flexural strength of 21.936 MPa, a modulus of 2.083 GPa, and a hydrophilic contact angle of 73.73 degrees. Cell survival tests confirmed biocompatibility, with a survival rate exceeding 70% and no toxicity. These findings highlight the potential of PLA/PCL/ACP composites, combined with injection molding, for developing biodegradable root canal posts in primary teeth.